Night Tourism in Indonesia 2023 - Awaloedin, Dipa Teruna; Putrandally, Jevanda; Hibatullah, M Rafif; Pradini, Gagih; Agustiani, Fitri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Tourism research on night tourism has developed in recent years. However, few still provide a global picture of the concept. This study aims to identify trends in tourism at night as well as other scientific products over time, such as source, author, and type of document. Bibliometric analysis was used to analyze a sample of 156 articles from Google Scholar published in 2023. Night tourism is the main keyword used in article titles, abstracts, and keywords to get metadata retrieved from the Google Scholar bibliographic database, on Friday, October 20, 2023. The tools used in bibliometric analysis are Microsoft Excel which is used to perform frequency analysis, VoS viewer for data visualization, and Harzing's Publish or Perish used for citation and analysis metrics. The results of this study show that the majority of related articles are published in scientific journals, compared to others. Related articles published in scientific journals have obtained the highest citations compared to others. Articles are also found in English.  Based on network visualization the most dominant terms (often appearing) are "" and "sustainable tourism". When viewed from the Overlay Visualization, the topic of "communities-based tourism" shows the latest trends in research related to "rural communities".